Electromyographic fatigue threshold of the biceps brachii: The effect of endurance time - Oliveira, A. S C [UNESP]; Cardozo, A. C. [UNESP]; Barbosa, F. S S [UNESP]; Gonçalves, M. [UNESP] (My University, 2007)
Muscle fatigue can be a limiting factor to determine index as the electromyographic fatigue threshold (EMGFT) due the alterations in motivation and disconfots. This way, the purpose of this study was to identify the right biceps brachii and left biceps brachii obtained from repetitive elbow flexions at each 10% of total time. Nine healthy subjects performed the exercise named biceps curl until exhaustion with 25%, 35%, and 45% of one repetition maximum, in three different days. EMG amplitude (root mean square - RMS) was obtained for concentric contractions during these load levels and correlated with time to determine the slope values for each load and them detemine the EMGFT. The EMGFT was obtained within of each 10% of total time and they were compared by analysis of variance. The results showed a progressive increase in RMS with time, for both muscles in all loads, characterizing the muscle fatigue process, and for the EMGFT values ware not found predominantly significant differences between the execution time, as well as between muscles (right biceps × left biceps). This protocol allowed to identify the EMGFT to both muscles during the biceps curl, which was similar at different percentage of total time, indicating the possibility to reduce the length of the contraction test without the need to maintain the contraction until exhaustion. Further studies are needed to evaluate the applicability of this method to determining the effects on performance.
Keywords: Biceps brachii; Dynamic contraction; Electromyography; Fatigue threshold; Muscle fatigue; adult; analysis of variance; biceps brachii muscle; clinical protocol; controlled study; elbow flexion; electromyography; exhaustion; human; human experiment; male; muscle contraction; muscle exercise; muscle fatigue; muscle function; normal human; time; Adult; Arm; Differential Threshold; Exertion; Humans; Male; Muscle Fatigue; Muscle, Skeletal; Physical Endurance; Time Factors; Weight Lifting